Impact of deep oropharyngeal suctioning on microaspiration, ventilator events, and clinical outcomes: A randomized clinical trial. (7th August 2019) - Sole, Mary Lou; Talbert, Steven; Yan, Xin; Penoyer, Daleen; Mehta, Devendra; Bennett, Melody; Emery, Kimberly Paige; Middleton, Aurea; Deaton, Lara; Abomoelak, Bassam; Deb, Chirajyoti
Abstract: Aims: To evaluate a deep oropharyngeal suction intervention (NO‐ASPIRATE) in intubated patients on microaspiration, ventilator‐associated events and clinical outcomes. Design: Prospective, two‐group, single‐blind, randomized clinical trial. Methods: The study was conducted between 2014 ‐ 2017 in 513 participants enroled within 24 hr of intubation and randomized into NO‐ASPIRATE or usual care groups. Standard oral care was provided to all participants every 4 hr and deep oropharyngeal suctioning was added to the NO‐ASPIRATE group. Oral and tracheal specimens were obtained to quantify α‐amylase as an aspiration biomarker. Results: Data were analysed for 410 study completers enrolled at least 36 hr: NO‐ASPIRATE ( N = 206) and usual care ( N = 204). Percent of tracheal specimens positive for α‐amylase, mean tracheal α‐amylase levels over time and ventilator‐associated events were not different between groups. The NO‐ASPIRATE group had a shorter hospital length of stay and a subgroup with moderate aspiration at baseline had significantly lower α‐amylase levels across time. Conclusion: Hospital length of stay was shorter in the NO‐ASPIRATE group and a subgroup of intervention participants had lower α‐amylase across time. Delivery of standardized oral care to all participants may have been an intervention itself and possibly associated with the lack of significant findings for most outcomes. Impact: This trial compared usual care to oral care with a deep suctioning intervention on microaspiration and ventilator‐associated events, as this has not been systematically studied. Further research on the usefulness of α‐amylase as an aspiration biomarker and the role of oral suctioning, especially for certain populations, is indicated. Trial registration number: ClinicalTrials.gov: NCT02284178. Abstract : 目的: 评估插管患者的深口咽吸干预(非吸入)对微量误吸、呼吸机事故以及临床结果的影响。 设计: 前瞻性、两组、单盲、随机临床试验。 方法: 这项研究在2014年至2017年期间进行, 513名实验对象在插管24小时内进行了登记, 并被随机分为非吸入组或常规护理组。 每4个小时为所有实验对象提供一次标准的口腔护理, 并将深口咽吸加入非吸入组。用口腔和气管标本量化了α‐淀粉酶作为误吸生物标本。 结果: 对410名至少登记超过36小时的实验对象的数据进行了分析:未抽吸(N = 206)和常规护理(N = 204)。气管标本阳性α淀粉酶的比例即随着时间推移的气管α‐淀粉酶水平与呼吸机相关事故两组间并无差别。非吸入组的住院时间更短, 且基线误吸更少的子群随着时间推移明显降低了α‐淀粉酶水平。 结论: 非吸入组的住院时间更短, 随着时间推移干预子群的实验对象α‐淀粉酶水平明显降低。向所有参与者提供标准化口腔护理本身可能就是一种干预并可能与大部分结果缺乏重大发现有关。 影响: 由于尚未得到系统研究, 本次试验就微量误吸的深咽干预和呼吸机相关事故将常规护理和口腔护理进行了对比。需要对α‐淀粉酶作为误吸生物标本的有效性以及口腔吸入的作用, 尤其是对特定群体而言的作用, 进行进一步研究。 试验注册编号: 临床试验。政府:NCT00654321。